Pemeriksaan Mukoskeletal pada Lansia di Desa Widodomartani, Ngemplak, Sleman, D.I Yogyakarta - Rosdewi, Naomi Nisari; Puspitawati, Theresia; Meisatama, Herta (Jurnal Pengabdian Dharma Bakti, 2020)
Increased Life Expectancy has an impact on increasing the number of elderly people. Older people are part of a society that cannot be solved in our lives. Widodomartani Village, Ngemplak Subdistrict, Sleman DIY is one of the villages that has a high number of elderly people. Some of them still remain productive in their old age. This needs to be maintained and improved, considering that the elderly are the age group that is susceptible to disease. Promotive and preventive efforts are very important to do to improve the health of the elderly and to increase family expectations.Keywords: mucoskeletal, elderly, examination